Nekotorye teoretico-metodologicheskie aspekty etapnogo pedagogicheskogo kontrol'ya fizicheskogo sostoyaniya i podgotovlennosti sportsmenov - Rosin, E. Yu. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The aim of this paper was to consider the main aspects of the pedagogical testing in the interests of the athletes' physical state and preparadeness control at different stages of their many years training. The author analyses the basic concepts of testing's and control's theory: the diagnosis, the stage pedagogical testing, the normal demands, the proper norms, the model characteristics, the prognosis and the prognostication. The alternative methods of the forecasting are discussed. The essence of the prospecting method of forecasting for the stage testing of the athletes' physical state is analysed. The normal forecasting is considered on the example of the "tree of aims" method.